GARBAGE, SURVIVAL AND HEALTH: CATCHING A COMMUNITY’S SEXUAL AND REPRODUCTIVE HEALTH IN A LANDFILL: GARBAGE, SURVIVAL AND HEALTH: CATCHING A COMMUNITY’S SEXUAL AND REPRODUCTIVE HEALTH IN A LANDFILL - Feitosa, Ankilma do Nascimento Andrade; Rodrigues, Francisca Lourenço; Medeiros, Renata Lívia Silva Fonsêca Moreira de; Quental, Ocilma Barros de; Nascimento, Ingridy Michely Gadelha do; Oliveira, Geane Silva (Brazilian Journal of Production Engineering, 2020)
Over the years, sexual and reproductive health and sexuality have led to valuable discussions, making the preponderance of debate regarding sexual health pertinent in different settings, including in landfills, a place conducive to a complexity of pathologies. Objective: To know the aspects that involve the sexual and reproductive health of this population. Method: This is a field study, exploratory-descriptive, with qualitative and quantitative approach. The research was carried out in a landfill, had a population of thirty people, residents of the landfill. Sample was made up of those who fit the inclusion and exclusion criteria totaling 22 people. The interview was guided by a research instrument developed by the researcher. The collection took place in September and October 2018. The socio-demographic data were analyzed using absolute frequency, percentile and displayed in a table, the ones referring to the objectives were through content analysis, thematic modality of Laurence Bardin. Results: Most of the participants have previous knowledge, however superficial of what STIs are, as some responded that STIs are related to HIV/AIDS, still mistakenly associated safe sex with the use of contraceptives, while others only use condoms. Oral contraceptives are prevalent, and most practice the main hygiene measures. Conclusion: The evidence leads to the conclusion of the contribution to the scope of health, as well as knowledge about the topic and population, bringing discussions to the academic world and arousing interest in new research. However, program formulations are necessary, in addition to comprehensive and systematic assistance based on the social determinants and health conditions of waste pickers.